Новый для фауны СССР вид рода нетелия — Netelia Gray (Hymenoptera, Ichneumonidae) — из Крыма - Толканиц, В.И. (Вестник зоологии, 1971)
Netelia decorator Seyrig previously known from Spain and Italy was found in
the Crimea first for the USSR. The main characters of the samples from the Crimea correspond to the first description except for the following: 1) occipital carina is developed
well (in the description — slightly); 2) the face narrows downwards (in the description —
square); 3) the peculiar male characters in coloration of face and thorax, mentioned in
the description are not the characters of sex because the females with similar coloration
are found. The typical characters of genitalia: the tip of squama is rounded, the brace at
the internal surface of the squama is curved and there is no pad, penis valves are straight
with apodemes curved at right angle. The egg is oval, chorion compact, black. Egg petiole is light with dark spot near the base.